Extensive Listening for Efl Students’ Listening Comprehension - Prastiyowati, Santi (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2018)
Assisting students to develop their listening fluency has been always a particularly difficult of foreign language teaching. Extensive listening, similar to extensive reading, focuses on meaning rather than form. The purpose is to provide students with as much target language input as possible. This study describes the teaching of extensive listening to English Department students of Muhammadiyah University of Malang. This paper highlights the difficulties found and the strategies applied by the students during the learning process. Questionnaires with close and open-ended questions were used as the research instrument as well as interview to gain the students? opinion while the data to identify the strategies used by the students were gathered from interview. The subject of this study was 12 students who join Basic Listening subject. The result of the study shows that the problems are related with listening materials, students? performance, and listening equipment. Regarding the strategy, this study reveals that students applied five tactics to comprehend the listening materials better. Those strategies are: giving pause and replay, guessing unknown words, finding difficult words in the dictionary, predict the content by using background knowledge, making notes or rewrite the text.